The Effect of CIRC (Cooperative, Integrated, Reading and Composition) Method on Students Achievement in Reading Recount Text - Mutia Nasution (research, training and philanthropy institution Natural Aceh, 2022)
This research aim is to know if there is a significant effect CIRC (Cooperative, Integrated, Reading, and Composition) Method of the tenth-grade students of SMA Negeri 1 Padangsidimpuan. The population is the tenth-grade students of SMA Negeri 1 Padangsidimpuan, which is consist of 250 students. Then, the sample is taken from the population by cluster random sampling technique and the total sample is 61 students. After calculating the data, it is found that the mean score of students reading recount text before taught by CIRC (Cooperative, Integrated, Reading, and Composition) method is 70; it is categorized as “enough”. While the mean score of students reading invitation letters after being taught by CIRC (Cooperative, Integrated, Reading, and Composition) method is 90, it is categorized as “good”. After finding the score of ttest and ttable, both of the scores are compared. It is found that the ttest is higher than ttable (ttest>ttable = 2,97 > 1,98) It means there is a significant effect of the CIRC (Cooperative, Integrated, Reading, and Composition) method on reading recount text of the tenth-grade students of SMA Negeri 1 Padangsidimpuan. So, the hypothesis in this research can be accepted.